Zoonotic parasites in feline coprolites from a holocenic mortuary context from eastern Patagonia (Argentina). (23rd July 2019) - Beltrame, María Ornela; Serna, Alejandro; Cañal, Victoria; Prates, Luciano
Abstract: Nowadays, wildlife is one of the most important sources of zoonoses, and it is a major concern for public health. Nevertheless, little is known about the role of wildlife as a reservoir and source of infectious diseases in the past. South America presents a wide diversity of wildlife. In the south of the continent, Argentina shelters a large diversity of neotropical carnivores. Although the paleoparasitological studies on carnivores have been increasing in southern Argentina, most of the efforts have been focused in a handful of sites located in western Patagonia. In this paper, two coprolites of felid found in Cueva Galpón, an initial late Holocene mortuary site from northeast Patagonia (Argentina), were studied for paleoparasitological purposes. Samples were processed by rehydration and homogenization, filtered and processed by spontaneous sedimentation. The samples were assigned to Puma concolor (puma) or Panthera onca (jaguar). Microscopic observations revealed that both coprolites were positive for parasite remains. High parasite richness was observed. Six nematodes, one cestode, and one coccidian morphotypes were reported. This is the first time that Gnathostoma sp. and Spirocerca sp. were recovered from holocenic times from Patagonia. This finding implies that some diseases such as taeniasis, spirocercosis, gnathostomosis, ascariasis, and coccidiosis could be present in holocenic wildlife from Patagonia prior to the Spanish colonization and domestic animal introduction. The overall results suggest that felids could have played a role as reservoirs and source of some parasitic species, some of which are zoonotic. Therefore, this animal could have entailed a risk agent for human health in the site.